Intra-Group Diversity and How it is Managed by an Outlaw Motorcycle Club - Wolf, Daniel R.; Young, David E. (Culture, 1983)
A deviant subculture such as an outlaw motorcycle club must be able to accommodate internal diversity because a repertoire of differing talents, ideas, and attitudes facilitates an adequate response to the disparate demands placed upon the organization. At the same time that intra-member variation is an asset, however, diversity frequently must be camouflaged in order to maintain the integration necessary to survive in a hostile environment. The need for camouflage varies in relation to the degree of perceived threat. This theme is examined in three different contexts: the clubhouse, the club bar, and violent encounters with outside society.